THE METHOD OF OPTIMIZATION OF THE SET OF TECHNICAL FACILITIES TO PROVIDE AVIATION SAFETY AND SECURITY - B. V. Zubkov; A. K. Volkov; A. K. Volkov (Научный вестник МГТУ ГА, 2016)
The actuality of problem of optimizing the set of technical facilities to provide aviation safety and security is determined by the necessity to develop aviation security provision system taking into account the analysis of threats while ensuring balance between expenses on security support and possible damage from the act of unlawful interference.The offered method of optimization consists of two main stages: determination of the optimal total expenses and determination of the optimal set of technical facilities.The first stage is devoted to analysing the threats and solving the task of optimization of total expenditures on the technical aids set used to ensure aviation safety and security which means searching for the minimum of total expenses goal function. These expenses constitute a sum of expenses spent on technical aids set and damage from the act of unlawful interference.The second methodological stage deals with setting the task of parameters synthesis. To solve this task it is necessary to determine the main features of the technical aids set, the criterion of the system operation quality and restrictions imposed on the system.Practical significance of the suggested method of optimization gives the possibility to solve the task of scientifically-grounded selection of technical aids set which is aimed at protecting from the acts of unlawful interference when guided by providing balance between expenses on aviation security and potential damage.